2012
DOI: 10.1111/mec.12052
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent, behavioural, and transcriptional variability of a tritrophic interaction consisting of bean, herbivorous mite, and predator

Abstract: Different organisms compensate for, and adapt to, environmental changes in different ways. In this way, environmental changes affect animal-plant interactions. In this study, we assessed the effect of temperature on a tritrophic system of the lima bean, the herbivorous spider mite Tetranychus urticae and the predatory mite Phytoseiulus persimilis. In this system, the plant defends itself against T. urticae by emitting volatiles that attract P. persimilis. Over 20-40 °C, the emission of volatiles by infested pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…Lodge et al 2012;Malek et al 2012;Orozco-terWengel et al 2012;Parchman et al 2012;Pompanon et al 2012;Tedersoo et al 2012), as well as new questions that have resulted from merging formally disparate disciplines (e.g. Kraaijeveld et al 2012;Nosil & Feder 2012;Ozawa et al 2012;Simms & Porter 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lodge et al 2012;Malek et al 2012;Orozco-terWengel et al 2012;Parchman et al 2012;Pompanon et al 2012;Tedersoo et al 2012), as well as new questions that have resulted from merging formally disparate disciplines (e.g. Kraaijeveld et al 2012;Nosil & Feder 2012;Ozawa et al 2012;Simms & Porter 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The risk assessment of non‐target effects, especially on beneficial species such as natural enemies, is crucial to apply this technology in an integrated pest management (IPM) program. Important natural enemies of spider mites, such as P. persimilis and M. occidentalis , have been found to be sensitive to oral RNAi . However, given the evolutionary distance between predatory mites and herbivore mites, we believe that sequence‐dependent unintended effects can be avoided, given the appropriate target gene design.…”
Section: From Laboratory To Field: An Example Of a Promising Mite Conmentioning
confidence: 99%
“…Important natural enemies of spider mites, such as P. persimilis and M. occidentalis, have been found to be sensitive to oral RNAi. [11][12][13]20 However, given the evolutionary distance between predatory mites and herbivore mites, we believe that sequence-dependent unintended effects can be avoided, given the appropriate target gene design. Evaluation of the specificity of RNAi silencing in mites and the potential for unintended effects on non-target organisms and investigation of whether bioinformatics could be a useful tool in risk assessment are necessary.…”
Section: Gene Silencing and Phenotypic Effects Induced By Dsrna In MImentioning
confidence: 99%
“…Likewise, high amounts of (E)-β-ocimene, α-farnesene, farnesyl cyanide and MeSA were collected from O. yothersi-infested avocado shoots(Table 1). The emission of farnesyl cyanide from mite-infested avocado plants constitutes the first report of the presence of this sesquiterpene in volatile profiles from mite-infested plants.Evidence indicates that temperatures and light are the main environmental factors controlling the dynamics of both BVOCs' and HIPVs' emissionsKigathi et al 2009; Staudt and Lhoutellier 2011) Ozawa et al (2012). found that lima bean (P. lunatus cv.…”
mentioning
confidence: 99%